Pengaruh Manajemen Konflik Terhadap Peningkatan Kompetensi, Motivasi, dan Kinerja Pendidik - Masjudin, Masjudin; Thohri, Muhammad; Na'amy, Nazar (Jurnal Manajemen & Budaya, 2024)
The aim of this research is to examine the effect of conflict management on the competence, motivation and performance of educators in MTs throughout the sub-district. This research uses a quantitative approach with survey methods. Data collection was carried out using a questionnaire with a total population and sample of 104 educators from 11 MTs in the sheet sub-district. Data analysis techniques use classical assumption tests and hypothesis testing uses simple and multivariate regression tests. The results of the research show that there is an influence of conflict management on competence as evidenced by the results of a simple regression analysis which obtained a Sig value. value 0.003 (0.003<0.05), the effect of conflict management on motivation is proven by the results of a simple regression analysis which obtained a Sig. The value is 0.029 (0.029<0.05), and the effect of conflict management on performance is proven by the results of a simple regression analysis which obtained a Sig. the value is 0.001 (0.001<0.05). Effective school principal leadership in implementing conflict management can contribute to increasing the competence of educators through the support and guidance provided.